Teori Dasar Pendidikan Multikultur dari Aspek Pengertian Sejarah dan Gagasan-Gagasannya - Sofiana, Fina; Wulandari, Tri; Wahidaturrahmah, Nurul; Asiyah, Asiyah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to reveal the basic concepts in multicultural education from the aspect of understanding, history and ideas. The type of research used is qualitative research with the technique used by researchers is literature study. The results of the research show that multiculturalism can simply be understood by acknowledging that a country or society is diverse and plural. On the other hand, the state does not only develop a single national culture. A multicultural education is expected to be able to solve conflict problems that occur in society, or at least be able to provide awareness to the community that conflict is not a good thing to be cultivated. In conclusion, education must be able to provide intellectual offerings, including by designing materials, methods to a curriculum that is able to make people aware of the importance of being tolerant of differences in ethnicity, religion, race, ethnicity and culture of the multicultural Indonesian society. Keywords: Ideas, multiculturalism, history, education